2013
DOI: 10.1021/es303804g
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Benefits of Nitrogen for Europe and Implications for Mitigation

Abstract: Cost-benefit analysis can be used to provide guidance for emerging policy priorities in reducing nitrogen (N) pollution. This paper provides a critical and comprehensive assessment of costs and benefits of the various flows of N on human health, ecosystems and climate stability in order to identify major options for mitigation. The social cost of impacts of N in the EU27 in 2008 was estimated between €75-485 billion per year. A cost share of around 60% is related to emissions to air. The share of total impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
175
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(184 citation statements)
references
References 29 publications
2
175
0
1
Order By: Relevance
“…In the air, it leads to the formation of ozone and particulate matter. Negative impacts on human welfare 1,7,12 include direct health damages like cancer and asthma, as well as the loss of ecosystem services, affecting for instance the productivity of aquatic ecosystems and hence fishing 13 . In monetary terms, Nr pollution is estimated to cause damages in the magnitude of 0.3-3% of global gross domestic product (GDP) 1 .…”
mentioning
confidence: 99%
“…In the air, it leads to the formation of ozone and particulate matter. Negative impacts on human welfare 1,7,12 include direct health damages like cancer and asthma, as well as the loss of ecosystem services, affecting for instance the productivity of aquatic ecosystems and hence fishing 13 . In monetary terms, Nr pollution is estimated to cause damages in the magnitude of 0.3-3% of global gross domestic product (GDP) 1 .…”
mentioning
confidence: 99%
“…No comprehensive study was found that sums up all hidden costs of IA. However, health costs caused by nitrogen fertilizers were estimated for Europe to range between 70 and 320 billion € each year, of which health costs and air pollution constitute about 75% [16]. These big amounts can be explained by the numerous effects of the degradation products of nitrogen fertilizer such as NOx, NH 3 , N 2 O and nitrate.…”
Section: Resultsmentioning
confidence: 99%
“…The social cost of all nitrogen pollution in the EU27 has been estimated at € 75-485 billion per year, of which close to half is attributed to health damage from SIA air pollution. 8 For the US, annual health costs of ammonia emissions associated with agricultural exports alone were estimated at US$ 60 billion. 9 Of course, abatement measures come at a cost -but the total cost for the proposed emission controls by agriculture are a mere 2-3% of the total emission control costs estimated for the complete package (about € 2.5 billion/year out of € 91 billion).…”
Section: Main Textmentioning
confidence: 99%